Problematika Guru dalam Penilaian Pembelajaran Kurikulum 2013 di SD Muhammadiyah 24 Surakarta Tahun 2016/2017 - Ningsih, Intan Dwi Astuti, Dra. Sri Hartini, S.H, M.Pd (2017)
This research aims to find out and describe:1) teacher problematic of learning assessment 2013 curriculum 2013 in SD Muhammadiyah 24 Surakarta, 2) factors that led to the learning assessment problems faced by teachers in the implementation of 2013 curriculum in SD Muhammadiyah 24 Surakarta, 3) solution that do teacher to address the problem of learning assessment of 2013 curriculum 2013 in SD Muhammadiyah 24 Surakarta. Data collection technique used are in-depth interview, observation, and dokumentation. The technique of the validity of the data used is a triangulation of sources and triangulation tevhnique. The result showed: 1) problematic competency attitude assessment sometimes attitude of student in not recorded, to techniques of self assessment and friends yet appropriate for lower class children, based on the assessment of the competence of the knowledge on the assignment (home work) competency assessment skills, problems in the allocation of time, 2) cause factor assessment of competence of its stance when the teacher was unable to attend, to knowledge caused by occasional students not doing homework, and skills because large number of student, 3) solutions that do, namely the teacher to coordinate with attitute oge of assessment teacher substitute, knowledge with koordination with the parents, and the skill portion of the students doing the performance in other learning. Thus, this research it can be concluded thet teacher in SD Muhammadiyah 24 Surakarta experience based learning assessment of 2013 curriculum on 2016/2017.